Behaviour disturbances during recovery from herpes simplex encephalitis. Issue 9 (September 1983) - Greenwood, R; Bhalla, A; Gordon, A; Roberts, J
Abstract : Bizarre behaviour disturbances in four patients occurring during incomplete recovery from herpes simplex encephalitis are described. Some aspects of their behaviour were similar to that originally described by Klüver and Bucy in monkeys following bilateral temporal lobectomy. Previous reports of behavioural disturbances in man after herpes simplex encephalitis are reviewed and attention drawn to the aggressive and disruptive behaviour that is often seen. With the reduced mortality in herpes simplex encephalitis in recent years it is possible that behaviour disturbances such as those described here will be seen more frequently.